EFFECT OF CO-ENZYME Q10 IN RECOVERY OF HISTOLOGICAL CHANGES OF LIVER IN RABBITS TREATED WITH IVERMECTIN (Academicia Globe: Inderscience Research, 2021)
The present study was designed to investigate the potential protective and prophylatic effect of Coenzyme Q10 against the Liver tissues affected by Ivermectin administration to rabbits . Forty-eight Healthy adult male albino rabbits approximately 13-14weeks old, ranging in weight from 1350 - 1800 grams were used in this study . The groups divided into six identical groups of 8 animals .group A = control. group B , C and D all rabbits receiving Ivermectin 2mg/kg weekly for 8 weeks , then after stopping Ivermectin B = Direct tissue slicing ,C = administer adaily dose of Coenzym q 10 10mg/kg for 30 days , D = rabbits Leave 30 days for self-healing . E =Ivermectin 2mg/kg weekly + Coenzym q10 10mg/kg daily for 8 weeks, F =only Coenzym q10 10mg/kg for 30 days. Results showed normal liver tissue in group A , C , E and F . Histopathlogical observations of group B and D showed damage in liver such as sever cell swelling with sever necrosis of hepatocytes ,heperplasia of epithelial cells lining bile ducts and congestion of blood vessels. The present study suggests firstable caution must be considered for Ivermectin administration. Second The Coenzym q10 almeliorate liver damage due to Ivermectin toxicity.